تێڕوانینی پیوریتانەكان بۆ بوارە جیاوازەکانی ژیان - شەریف, پ.ی.د. هیوا حمید; احمد, م.ی. دارەوان عبدالقادر (Sulaimani Journal for Humanities, 2023)
This study explores the Puritan worldview and general attitude towards life by considering their religious status and influence on politics, economics, society and culture. Although the Puritans had a complex identity with numerous ideological divergences, so far scholars have not followed a unified approach to understand in depth all the aspects of their beliefs and worldviews. Thus, our study aims to discuss and analyze the Puritans’ worldviews and their unique understanding towards different aspects of life to answer the following questions: how did the Puritans shape their religious, political, economic, social and cultural world? Was their religious faith reflected in other aspects of their life? What were their political views and desired form of government and to what extent were they able to form and implement their own unique political system? How did they manage to identify and overcome their social problems and were they able to solve their social issues and build a healthy society based on their ideals? What economic reforms did they implement that led to the establishment of a capitalistic system and how did they integrate their religious faith into businesses to achieve economic growth? Similarly, was the Puritans’ view of culture solely rooted in their religious beliefs and why were any cultural activities and rituals that were not compatible with puritan faith banned? This paper seeks to answer these questions by examining the long-established discourses around the of Puritan worldviews and values using sound historical evidence to reach the fundamental truth about the importance of the puritanism as one of the most influential movements in Christianity in general and Protestantism in particular that played a critical role in founding the United States of America (USA).
Keywords: Puritan; worldview; Christianity; Protestantism; church